The Role of Handicrafts in the Sustainable Development of Rural Tourism with an Emphasis on Indigenous Knowledge - Hosseinnia, Elham; Shoja, Baharak (International Journal of Geography and Geology, 2016)
Tourist is a process that had been existed a long period of time with different forms in human societies and has gradually solved its historical and evolutionary processes. As the tourism has influenced in the economic, social and cultural countries that economists have called it as an invisible export. On the other hand, rural tourism is one of the most important subgroups of the development of tourism in each region that nowadays is considered one of the most popular forms of tourism and in the form of tourist activity takes place in the village. Descriptive and analytic study based on library studies and documents. At first, we evaluated the quality and importance of Indigenous knowledge and sustainable development with the approach of tourism and with regard to conceptual framework and fundamental issues related to rural handicrafts and tourism. Then, findings from the study In relation to effects of Socio - economic Handicrafts tourism development in Iran were extracted and analyzed by the research subject. And the results show, by combining "Indigenous knowledge" and "modern knowledge “and regarding to existence of rural conditions such as Indigenous areas , taking into account the resources , the potential and conditions of each region can be acquired grounds for an favorable model from sustainable rural development. Despite the frequency of human resources in rural areas, the Lack of water and land push on farmland and cause to migration of labor efficient from rural to urban areas where efficiency is reduced because of lack of expertise. Therefore, in rural areas where there are no grounds for agriculture that can be used the non-farm economy, "such as local industries, etc.”